Ultrasound-Assisted Melt Extrusion of Polymers with the Main Harmonics of 10–60 kHz - Diana Agüero-Valdez; Alain González-Sánchez; María Teresa Rodríguez-Hernández; Heidi Andrea Fonseca-Florido; Juan Guillermo Martínez-Colunga; Janett Anaid Valdez-Garza; Gilberto Francisco Hurtado-López; Víctor Javier Cruz-Delgado; Carlos Alberto Ávila-Orta (Fluids, 2025)
Using a digital oscilloscope, the main harmonics resulting from the application of different frequencies and power levels of ultrasonic waves during the polymer extrusion process were identified. The primary harmonics are located between 10 and 60 kHz and exhibit unique characteristics, such as shape, crest, and trough, the latter being associated with voltage and current. The crest-to-trough distance (height) observed during processing at 34 kHz and 375 W shows the highest value, which correlates with the highest melt flow index and the lowest apparent viscosity. It is well known that the application of ultrasonic waves can randomly break C-C bonds in hydrocarbon compounds, leading to a decrease in molecular weight. However, the application of ultrasonic waves at different frequencies and power levels can promote chain scission in both high- and medium-molecular-weight polymer chains, thereby increasing the molecular weight distribution. This phenomenon can lead to chain disentanglement, along with chain scission, as evidenced by a decrease in molecular weight at medium power and frequency intensities. Finally, a schematic representation of the interaction between polymer chains and ultrasonic waves is proposed.